PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA PT CAHAYA ECO INDONESIA DI BATAM - Susanti (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
The purpose of this research is to find out whether product quality and brand image have an effect on purchasing decision at PT Cahaya Eco Indonesia in Batam by using slovin formula as sampling technique so as the number of sample is 110 respondents. Methods of data collection is by using questionnaires.The data collected were analyzed using multiple linear regression analysis with the help of SPSS 25. The results of determination (R2) obtained by product quality and brand image variables of 40,9% of purchasing decisions. The result of double linear regresion test, showing that product quality (X1) have a impact as much as 28,6% toward purchase decision (Y) and Brand Image(X2) have a impact as much as 48,4% toward purchase decision.Result of t test concluded that product quality and brand image have positive and significant effect to purchasing decision at PT Cahaya Eco Indonesia in Batam. F test results concluded product quality (X1) and brand image (X2) together affect the purchasing decision (Y) at PT Cahaya Eco Indonesia in Batam